Sequence features of variable region determining physicochemical properties and polyreactivity of therapeutic antibodies. (August 2019) - Lecerf, Maxime; Kanyavuz, Alexia; Lacroix-Desmazes, Sébastien; Dimitrov, Jordan D.
Highlights: The process of development of therapeutic antibodies is complex. Many antibodies fail to reach clinic because of inappropriate physicochemical behaviour. Assessment of physicochemical parameters of antibodies and identification of problematic molecules is of great importance. Physicochemical properties of antibodies relevant for development depend of the sequence features of variable region. Discovered sequence correlates may contribute for early identification of antibodies with developability issues. Abstract: Therapeutic antibodies have transformed the clinical practice. Not surprisingly, development of antibody therapeutics is currently the main focus of the biotechnology industry. Nonetheless, the development process is complex, and many antibodies do not reach the clinic. Reasons for the failures include, undesired binding behavior (polyreactivity), low stability, poor expression yields, unfavorable pharmacokinetics etc. Numerous studies have proposed different analytical methods for assessment of physicochemical parameters of antibodies and identification of problematic molecules at early stages of the development process. These studies, however, have not addressed the basic mechanistic question of how sequence features of variable regions determinate the different biophysical characteristics and the binding behavior of the antibodies. In a recent study, Jain et al assessed 12 biophysical qualities of 137 monoclonal therapeutic antibodies. We used the raw data from this comprehensive study to perform correlation analyses of different biophysical measurables with various sequence features of variable regions of the antibodies - number of mutations, length of hypervariable loops, and frequency of amino acid residue types. The obtained data reveled significant relationships between the sequence characteristics of the variable domains and different physiochemical properties of antibodies. The data from this study can assist in design of a set of criteria for early identification of antibodies with developability issues. Moreover, our findings provide novel fundamental insights into the sequence-function relationship of antibodies.